2016
DOI: 10.1371/journal.pntd.0004803
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Scabies and Impetigo in the Solomon Islands: A Population-Based Survey

Abstract: BackgroundScabies and impetigo are common, important and treatable skin conditions. Reports from several Pacific island countries show extremely high prevalence of these two conditions, but for many countries, including the Solomon Islands, there is a paucity of epidemiological data.MethodologyTen rural villages in the Western Province of the Solomon Islands were included in the study, chosen so that data collection could be integrated with an existing project investigating clinical and serological markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
102
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 21 publications
(31 reference statements)
14
102
9
2
Order By: Relevance
“…In American Samoan children with scabies, 53% of them had a bacterial superinfection . In the Solomon Islands, 41.1% of patients with impetigo also had scabies . The close relationship between scabies and skin bacterial colonizations and superinfections was demonstrated by two studies which were performed in an Australian Aboriginal community and the Solomon Islands, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In American Samoan children with scabies, 53% of them had a bacterial superinfection . In the Solomon Islands, 41.1% of patients with impetigo also had scabies . The close relationship between scabies and skin bacterial colonizations and superinfections was demonstrated by two studies which were performed in an Australian Aboriginal community and the Solomon Islands, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Skin bacterial colonizations and superinfections in patients with scabies are very common in some tropical and subtropical countries. Several studies have been carried out in India, 1,2 some countries of Pacific area (Fiji, [3][4][5] Australia, [6][7][8][9][10] and Solomon Islands 12,13 ), and Trinidad. 14 However, only very rare epidemiologic-bacteriologic studies have been performed in immunocompetent patients with scabies living in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with Nair et al [8] that they are proved there were 52 patients (50.98%) were males and 50 patients (49.01%) were females in Gujarat, India. Also, Mason et al [7] demonstrated that out of total 515870 patients infected with scabies in Solomon Islands there were 51.3% males and 48.7% females. In Iraq, in Tikrit Governorate in 2009, Alsamarai [16] proved that out of total 11194 patients infected with scabies there were 13.5% and 8.6% were male and female, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with scabies suffer from skin redness and severe itching in different body parts such as arms, legs and between the thighs [4,5]. Most patients infected with this disease are lived in rural areas without health care and without health awareness [6][7][8]. About more than 100 million patients infected with scabies worldwide [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities for integration range from diagnosis and surveillance to mass drug administration and morbidity management. These activities have already been successfully combined with existing programmes for trachoma and yaws in the Solomon Islands for the purpose of coordinating mass treatment studies [91]. Initiatives to support the provision of oral ivermectin for scabies are needed in low-resource settings, in the way that the Mectizan Donation Program provides for onchocerciasis and lymphatic filariasis.…”
Section: Strategy For Scabies Controlmentioning
confidence: 99%